Defining competency in flexible cystoscopy: a novel approach using cumulative Sum analysis. Issue 1 (December 2016) - MacKenzie, Kenneth; Aning, Jonathan
Abstract Background Flexible cystoscopy (FC) is one of the most frequently performed urological intervention. Cumulative sum analysis (CUSUM) allows objective assessment of a proceduralist's performance to ensure acceptable outcomes. This study investigated the application of CUSUM to assess a trainee's learning curve and maintenance of competence in performing FC. Methods A single urology trainee, with no previous experience of FC, performed FCs between August 2013 and February 2014. For assessment FC was divided into 5 steps. Each step was assigned a CUSUM completion score. The primary outcome measure was successful performance of a complete FC. Prospective data were collected and analysed using CUSUM. Results In total, 419 FCs were performed. Acceptable performance of FC was achieved by the 122nd procedure. Complete assessment of the ureteric orifices and trigone was the most difficult step of FC to achieve consistently. Competence for complete FC was achieved following 289 procedures. Conclusion CUSUM analysis objectively assesses acquisition of competence in flexible cystoscopy. Recommended indicative numbers may underestimate the number of FCs trainees require to achieve, and maintain, competency. Validation of CUSUM method in a larger cohort of trainees should be considered.